(3fRgI GdCacGQ Edi eYQaI GdSGOI GdGNjGQ ef GdSGOI GdUMGHI hGdJGHYjf hGdGhdjGA GdGHQGQs - (3CHh ESMGb EHQGgje Hf Ydj Hf jhSa GdajQhRGHGOi GdTjQGRis; (3GdajQhRGHGOj GdTjQGRj , CHh ESMb EHQGgje Hf Ydj GdTjQGRj, CHh GSMGb , LeGd GdOjf,J (B476 (3g` s
(3ChdgG (B:s
(3eNJUQ ai PcQ GdabgGA hGfSGHge heHdZ GYeGQge hhbJ haGJge s
(3ai WHbGJ GdabgGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B274 s
(3eUOQ GbJfGA GdCUd (B:s
(3Yehei (B(5302) s
Keywords: (3GdJGQjNs